Hellenic National Defense Forces: Embracing change to win. Issue 6 (2nd November 2019) - Ploumis, Michail
Abstract: Socio-economic factors have begun to upset the balance of military power between Greece and Turkey, a key defense strategy which Greece has relied upon to maintain peace with its neighbor. Provided that current trends continue, it is estimated that Greece will have difficulties in matching symmetric military Turkish threats in the near future. As such, the present article recommends a three-phase model to bring change in culture and doctrine within the Hellenic National Defense Forces, and thus aims to trigger innovative solutions that will allow Greece to confront Turkey's extensive armament programs before the balance of power reverses in Turkey's favor.Victory smiles upon those who anticipate the change in the character of war, not upon those who wait to adapt themselves after the changes occur. Giulio Douhet, 1869-1930.